2021
DOI: 10.3389/fpsyt.2021.805528
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination Rates in a Cohort Study of Patients With Mental Illness in Residential and Community Care

Abstract: Background: Patients with mental illness are at increased risk for COVID-19-related morbidity and mortality. Vaccination against COVID-19 is important to prevent or mitigate these negative consequences. However, concerns have been raised over vaccination rates in these patients.Methods: We retrospectively examined vaccine uptake in a large sample of Belgian patients admitted to or residing in a university psychiatric hospital or community mental health care setting between 29th of March 2021 and 30th of Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
(42 reference statements)
2
11
0
3
Order By: Relevance
“…This effect was largely due to in-hospital vaccination programs in some of the participating institutions, where patients hospitalized for mental illness got weekly vaccination offerings. Thereby, these routine care results confirm studies, which attributed lower vaccination rates in those with mental illness mainly to access barriers and not to a generally higher vaccination unwillingness [10][11][12][17][18][19]24]. They highlight the need to offer people with mental disorders repeatedly and actively COVID-19 vaccinations at all those health care providers, where they are in trusting and stigmatization-free contact with the health care system, thus psychiatric hospitals, outpatient clinics, and office-based psychiatrists and not only at centralized vaccination facilities or somatic medicine providers.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This effect was largely due to in-hospital vaccination programs in some of the participating institutions, where patients hospitalized for mental illness got weekly vaccination offerings. Thereby, these routine care results confirm studies, which attributed lower vaccination rates in those with mental illness mainly to access barriers and not to a generally higher vaccination unwillingness [10][11][12][17][18][19]24]. They highlight the need to offer people with mental disorders repeatedly and actively COVID-19 vaccinations at all those health care providers, where they are in trusting and stigmatization-free contact with the health care system, thus psychiatric hospitals, outpatient clinics, and office-based psychiatrists and not only at centralized vaccination facilities or somatic medicine providers.…”
Section: Discussionsupporting
confidence: 82%
“…Studies on vaccination rates of populations with mental illness in comparison to the general population showed heterogenous results: In some studies vaccination rates were comparable to or better than the general population [10][11][12][13] but in others people with mental illness showed much lower vaccination rates [14][15][16][17]. A common factor for vaccination rates similar to the general population seemed to be vaccination offerings by mental health institutions [10][11][12]. This corresponds to studies on reasons for non-vaccination that did not show a general vaccine hesitancy among people with mental illness but were organizational access issues appeared to be the most relevant factors [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies exploring vaccine uptake in SMI have borne mixed findings, with high regional variability, a recent study found that a targeted vaccination programme for patients in the community with SMI showed similar rates of vaccine acceptance to the general population, indicating people with SMI accept vaccination when given support to access it. 5 This suggests that our findings are not primarily because of reluctance to receive a COVID‐19 vaccine amongst people with SMI. Our finding that 20% of the patients who had not received a vaccine were waiting for support and 8.9% of patients were not yet invited to receive the vaccine is consistent with this.…”
mentioning
confidence: 78%
“…People with mental disorders, especially severe mental illness, have shown higher rates of COVID-19 morbidity and mortality ( 1 ); therefore, vaccination against COVID-19 should be prioritized for this vulnerable group, and this has already been assured in several countries ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%